Nutrient and specification enhancement of fortified Asian noodles by chickpea flour substitution and transglutaminase treatment. Issue 1 (1st January 2021) - Han, Lihong; Lu, Zhan-Hui; Zhang, Jiajia; Chakravarty, Bipasha; Jin, Lanyi; Cao, Xiaohong
ABSTRACT: Effects of supplementation of chickpea flour (CF) (10% and 20%) to wheat flour (WF) followed by Transglutaminase (TGase) treatment (0–1.2%) were investigated to synergistically boost nutritional and texture properties of Asian noodles. The results showed that CF supplementation diluted both gluten-forming proteins and starch content of the blend, resulting in the weak dough, high cooking loss, and poor sensory quality. However, TGase treatment at 0.4–0.8% dosage could effectively recover the dough structure by crosslinking, including CF proteins as evidenced by Mixolab, SDS-PAGE, and dynamic viscoelasticity. The latter also distinguished the distinct dough structure treated by TGase from the wheat gluten-network. SEM revealed the improved network matrix and well-embedded starch granules in raw and cooked noodles. The cooked noodles substituted with 10% CF with 0.4% TGase treatment had the lowest cooking loss and comparable sensory qualities to WF control ( p < .05).